Pandemic Impact on Population Structure - V. Ezepchuk Yurii; N. Skuratovskaya Larisa (International Journal of Coronaviruses, 2022)
The victims of the first wave of the pandemic caused by the coronavirus Covid-19 were tens of millions of people in the population inhabiting the Earth. A previously unknown strain of Covid 19, which has a specific affinity for lung tissue and high contagiousness, has demonstrated a global danger to the life of the population of the entire planet. The pathogenicity of the virus is due to a three-segment structure, in which the RNA-containing segment, which is a pathogenicity factor responsible for specific lesions, most likely has an enzymatic nature.
Keywords: coronavirus